Talaromyces omanensis sp. nov.: phenotypic and molecular characterization of a novel species isolated from Rhazya stricta in Oman - Halo, Boshra A.; Maharachchikumbura, Sajeewa S.n.; Al-Yahyai, Rashid A.; Al-Nabhani, Abdulrahman A.; Al-Sadi, Abdullah M. (Phytotaxa, 2019)
The endophytic Talaromyces omanensis sp. nov., a new microfungus isolated from the desert plant Rhazya stricta in Oman, is described and illustrated. The new species forms a distinct sister clade to the section Subinflati in the phylogeny of internal transcribed spacer (ITS), β-tubulin (benA) and Calmodulin (CaM). Talaromyces omanensis remains distinct and unique from the other species in the section Subinflati in having monoverticillate conidiophores.